The use of social media for professional purposes among dentists in Saudi Arabia - Khalifa S. Al-Khalifa; Abdullah S. Al-Swuailem; Rasha AlSheikh; Yasmeen Y. Muazen; Yazeed A. Al-Khunein; Hassan Halawany; Khalid S. Al-Abidi (BMC, 2021)
Abstract Aim To investigate the dentists' opinions towards social media (SM) use in daily practice and the expected limitations from its use in Saudi Arabia. Methods An electronic survey was carried out throughout May-June 2020 among a sample of dentists in Saudi Arabia. The survey covered three parts: the first part covered professional and demographic information, the second part covered the use of mobile phones and SM in dental practice, while the third part assessed dentists' opinion on SM use. Descriptive statistics included frequency distributions and percentages and independent t test/ANOVA test for the relationship between the mean of dentists' opinion towards SM and demographic variables. A p value of 0.05 or less was considered statistically significant. Results The majority of respondents (80%) believe that SM plays an active role in patients' decisions regarding the selection of a healthcare provider. The mean dentists' opinion scores on the use of SM were significantly lower among participants working more than 50 h per week compared with other participants (p = 0.014). Conclusion The majority of sampled dentists believe that SM plays an active role in patients' decisions regarding the healthcare provider's selection. Directed campaigns can help dentists optimize the use of SM for both professional and personal purposes.